1991
DOI: 10.1073/pnas.88.6.2156
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C mediates x-ray inducibility of nuclear signal transducers EGR1 and JUN.

Abstract: The cellular response to ionizing radiation includes growth arrest and DNA repair followed by proliferation. Induction of immediate early response genes may participate in signal transduction preceding these phenotypic responses. We analyzed mRNA expression for different classes of immediate early genes (JUN, EGRI, and FOS) after cellular x-irradiation. Increased expression ofthe EGRI andJUN genes was observed within 0.5-3 hr following x-ray exposure. Preincubation with cycloheximide was associated with superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(99 citation statements)
references
References 40 publications
5
94
0
Order By: Relevance
“…[1][2][3] Irradiation-induced increases in VEGF and other cytokines, 18-21 and inflammatory response genes have been reported. 19 Previously, we demonstrated that mice injected 24 h before irradiation with MnSOD-PL complex had decreased cytokine mRNA levels for IL-1 and TGF-␤ at 24 h, and TNF-␣ increase at 48 h compared with irradiated control. [1][2][3] In the present study we detected at 24 h after irradiation, increases in TGF-␤3, IL-1␤, MIF and IL-1R␣ in normal lung and these levels were reduced by C57BL/6J mice were IT-injected with 5 × 10 5 3LL-LacZ cells.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3] Irradiation-induced increases in VEGF and other cytokines, 18-21 and inflammatory response genes have been reported. 19 Previously, we demonstrated that mice injected 24 h before irradiation with MnSOD-PL complex had decreased cytokine mRNA levels for IL-1 and TGF-␤ at 24 h, and TNF-␣ increase at 48 h compared with irradiated control. [1][2][3] In the present study we detected at 24 h after irradiation, increases in TGF-␤3, IL-1␤, MIF and IL-1R␣ in normal lung and these levels were reduced by C57BL/6J mice were IT-injected with 5 × 10 5 3LL-LacZ cells.…”
Section: Discussionmentioning
confidence: 90%
“…This interval was chosen since previous studies suggested that the induction of some early response genes activated by ionising radiation occurred within 0.5-3 hr postexposure to radiation. 8,9 Twenty of 234 genes (12%) blotted on the array filter showed a difference in between S40b and MGH-U1 in at least 1 of the 2 independent experiments (Table II). It was of some concern that the differential gene expression pattern appeared to be inconsistent for some genes in the repeat experiments (e.g., NM23-H1).…”
Section: Discussionmentioning
confidence: 99%
“…5,6,14 The radio-responsive enhancer, containing four 'CArG' elements, has been identified in the 5Ј distal region of the Egr1 promoter. 9,10 In the current study, this Egr1 enhancer (in the plasmid pNGFP) was found to induce a 1.67-fold increase in reporter gene expression in MCF-7 cells after a single radiation dose of 5 Gy (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] These genes include those encoding the human tissue-type plasminogen activator, tumour necrosis factor alpha (TNF-␣) and early growth response protein 1 (Egr1). 8,9 Transcriptional activation of the Egr1 gene by ionising radiation appears to be a direct consequence of the production of reactive oxygen intermediates.…”
Section: Introductionmentioning
confidence: 99%